Financing the Development of Awqaf Property (American Journal of Islam and Society, 1999)
This article identifies the various ways in which Islamic endowments helped provide essential services for public welfare during the heyday of Islamic civilization. Four goals are essentially accomplished. One, the importance of endowments in an Islamic society is identified. Two, the various fonns of funding that have been used in the past for estab lishing Islamic endowments are explored. Three, the ways in which Islamic endowments can be expanded and new funds raised are examined. Finally, the author proposes ways by which public sources can be used to create new sources of funding for awqaf properties. He hopes that these new means can play a major role in developing contemporary Muslim societies.